Compound glycyrrhizin plus conventional therapy for psoriasis vulgaris: a systematic review and meta-analysis of randomized controlled trials. (1st February 2017) - Yu, Jason Jingjie; Zhang, Claire Shuiqing; Coyle, Meaghan E.; Du, Yiqi; Zhang, Anthony Lin; Guo, Xinfeng; Xue, Charlie Changli; Lu, Chuanjian
Abstract: Background: Psoriasis vulgaris is a chronic skin condition affecting patients' quality of life. Long-term use of conventional therapy increases risk of unwanted side effects. Compound glycyrrhizin in conjunction with conventional therapy has been used in clinical practice, but the evidence for such practice has not been evaluated systematically. Objective: This review aims to evaluate the efficacy and safety of compound glycyrrhizin in combination with conventional therapy for psoriasis vulgaris. Methods: PubMed, Excerpta Medica dataBASE (Embase), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Central Register of Controlled Trials, Allied and Complementary Medicine Database (AMED), CiNii, Chinese Biomedical Literature, China National Knowledge Infrastructure, Chinese Scientific Journals Full Text Database and Wanfang Data were searched from their respective inceptions to July 2015. Randomized controlled trials comparing compound glycyrrhizin plus conventional therapy to conventional therapy alone for psoriasis vulgaris were included. Data analysis was performed using Review Manager 5.3. Results: Eleven randomized controlled trials were included in this review. Meta-analysis of the 11 randomized controlled trials indicated that the addition of compound glycyrrhizin increased the number of patients achieving Psoriasis Area and Severity Index (PASI) 60 (RR: 1.30 [1.21, 1.40], I 2 = 6%), when compared with conventional therapy alone. Comparable numbers of patients experienced adverse events in the two groups. Conclusions: Compound glycyrrhizin in conjunction with conventional therapy enhances clinical response, and compound glycyrrhizin as add-on therapy does not appear to pose any additional risk in the treatment of psoriasis vulgaris. However, the findings should be interpreted with caution of methodological flaws in the included studies. PROSPERO registration number: CRD42015027763.